PERMISSIVE PARENTING AND PEER CONFORMITY WITH JUVENILE DELINQUENCY - Lestari, Sri Kusti Ningsih; Dewi, Salamiah Sari (Universitas Indraprasta PGRI, 2025)
The purpose of this study was to determine and analyze the relationship between permissive parenting and peer conformity with juvenile delinquency in SMP Negeri 5 Medan. The method used is a quantitative research method. The population in this study was 735 students. The sample used in this study was 205 students. The sampling technique used in this study used a purposive sampling technique. There is a significant positive relationship between peer conformity and juvenile delinquency from the coefficient value (Rxy) = 0.534, p = 0.000 < 0.050. The coefficient of determinant (R2) value has a value of 0.286, the conformity of students' peers in the school contributes 28.6% to juvenile delinquency in SMP Negeri 5 Medan. From the results of multiple regression analysis, it is known that there is a relationship between permissive parenting and peer conformity with juvenile delinquency. This is indicated by the coefficient F reg = 46.194 with p < 0.05, and the correlation coefficient R = 0.560 with p < 0.05 and R2 = 0.314; the contribution of permissive parenting and peer conformity in causing juvenile delinquency is 31.4%.